(untitled) (Ágora de Heterodoxias, 2026)
This review article offers a critical and structured synthesis of Acemoglu and Johnson’s Power and Progress: Our Thousand-Year Struggle for Technology and Prosperity (2023). The analysis focuses on the interaction between technology, institutions, power, and prosperity. On the one hand, it argues that technological development is not neutral, but rather the result of political and social decisions that shape the direction of change. On the other hand, through an interdisciplinary approach and analytical synthesis, it examines historical and contemporary lessons on how elites have shaped innovation to serve their own interests, and how inclusive institutions can counteract these dynamics. Finally, the article proposes pathways for democratizing technology and advancing toward truly shared prosperity.